2017
DOI: 10.1038/tp.2016.273
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic and GABAergic gene sets in attention-deficit/hyperactivity disorder: association to overlapping traits in ADHD and autism

Abstract: Attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASD) often co-occur. Both are highly heritable; however, it has been difficult to discover genetic risk variants. Glutamate and GABA are main excitatory and inhibitory neurotransmitters in the brain; their balance is essential for proper brain development and functioning. In this study we investigated the role of glutamate and GABA genetics in ADHD severity, autism symptom severity and inhibitory performance, based on gene set analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 71 publications
4
90
0
3
Order By: Relevance
“…Additionally, a direct and functional interaction between PICK1 and dopamine D 3 receptors (D 3 R) has been reported [57]. Furthermore, PICK1 has a role in glutamate receptor regulation [58], and a recent study revealed that a glutamate gene-set showed association with the severity of hyperactivity/impulsivity in an ADHD case-only sample [59]. In addition, adult Pick1 knockout mice show several behavioral abnormalities, such as hyperactivity and electrophysiological deficits in the prefrontal cortex [60].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a direct and functional interaction between PICK1 and dopamine D 3 receptors (D 3 R) has been reported [57]. Furthermore, PICK1 has a role in glutamate receptor regulation [58], and a recent study revealed that a glutamate gene-set showed association with the severity of hyperactivity/impulsivity in an ADHD case-only sample [59]. In addition, adult Pick1 knockout mice show several behavioral abnormalities, such as hyperactivity and electrophysiological deficits in the prefrontal cortex [60].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent analysis reported overrepresentation of glutamatergic GO in ADHD cases . A study that looked at both CNV as well as SNP in samples from five pooled ADHD studies in comparison to data from autism and schizophrenia found six enriched pathways that included plausible ones, such as ‘ligand‐gated ion channel activity,’ and more opaque ones, such as ‘respiratory electron transport.’ There was huge overlap between schizophrenia, autism, and ADHD.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…Reduced concentration of extracellular GABA has been detected in children with ADHD, therefore abnormal functioning GABAergic cells may be relevant to ADHD (43). Furthermore, a genetic association was uncovered between GABAergic genes and ADHD symptoms (Naaijen et al, 2017). These data suggest that the role of these cell types in ADHD should be further studied.…”
Section: Discussionmentioning
confidence: 99%